On Andropov‘s Question II: What Max Weber Would Answer to Yuri Andropov? - Norkus, Zenonas (Sociologija. Mintis ir veiksmas, 2008)
The paper is sequel to the article published in issue 1 (19) of this journal, continuing and concluding the analysis of the problem of the macrosociological diagnostics of communist societes. Present paper focuses on the concepts of communism as distinct way to (incomplete) modernity and communist neotraditionalism. Max Weber’s famous typology of the legitimate domination is considered as common source of these approaches, represented by Barrington Moore Jr. and Ken Jowitt. The author contributes to K.Jowitt’s Neo-Weberian analysis of the communist neotraditionalism and neopatrimonialism by spotlighting typological affinity of „socialist” economies to „oikos economy” as discussed by Max Weber. The author advances the proposal to solve the controversy between different approaches to the explanation of communism by limiting their validity claims by geographical and chronological scope conditions. The theory of communism as totalitarianism provides accurate phenomenological account of the characteristic features of the communist regimes during the early phase of their existence. However, during their late phases they have differentiated themselves into bureaucratic-authoritarian, national-accomodative and patrimonial types. The view of communism as a way into modernity is sufficiently accurate only with respect to the patrimonial and (partly) national-accomodative communism. At the same time, patrimonial communism is the type of communism that is marked by the most numerous premodern fe- atures.
Keywords: convergence theory; communist neotraditionalism and neopatrimonialism; Max Weber; Barrington Moore Jr.; bureaucratic-authoritarian; national-accomodative; and patrimonial communism